Oxigenoterapia relacionada à Escala de Aldrete e Kroulik e sinais vitais em pacientes em período de recuperação anestésica: ensaio clínico randomizado - Fiama Chagas Nunes (2016)
During the anesthetic recovery period, the patient is vulnerable to develop complications of the respiratory, cardiovascular, thermoregulation, integumentary, sensory, locomotor, urinary, digestive, and immune system, and changes in emotional state. Among the respiratory complications, the hypoxemia is the most common, presenting several levels of peripheral oxygen saturation below 95%. Objective: To compare the alterations of the values in Aldrete-Kroulik scale and vital signs related to the use of oxygen therapy in patients during the anesthetic recovery period. Method: It was a randomized clinical trial, performed with 98 subjects that were admitted to the post-anesthesia care unit of a public federal hospital in Belo Horizonte city (MG). From these 98 subjects, 49 belonged to the control group and 49 to the experimental group. For the subjects of the control group was delivered the routine interventions of the post-anesthesia care unit. To the experimental group was given oxygen therapy by nasal cannula, with flow rate of two liters per minute, from the admission of the patient in the post-anesthesia care unit until the stabilization of three parameter of the Aldrete-Kroulik scale (consciousness, respiration and peripheral oxygen saturation). The inclusion criteria were: adult patients, aged 18 64 years old, with status 1 or 2 from the American Society Anesthesiologists classification, submitted to elective surgery, under general anesthesia, general conventional surgery and specialties surgery, and presenting peripheral oxygen saturation greater than or equal to 95% at the moment when they were admitted in the post-anesthesia care unit. The data were analyzed using statistical guidance, and the ethical recommendations of the Ministry of Health for researches with humans were respected. Results: The sociodemographic and clinical aspects from the control and experimental group were homogeneous in relation to the gender. Most part was female, under surgery of the digestive system and breast. The most common comorbidities were "other comorbidities", followed by systolic arterial hypertension. About the American Society Anesthesiologists classification, most got status two (2), under total intravenous anesthesia. The length of time for the surgery, anesthesia and permanence in the post-anesthesia care unit were also homogeneous (p-value=0.422, p=0.565 e p=0.052), respectively. The groups were heterogeneous in relation to the age (p-value=0.003), and the experimental group presented the mean age higher than the control group. In the analysis of the parameters of Aldrete-Kroulik scale, the groups were homogeneous in relation to the consciousness and circulation, whereas the parameters for respiration were heterogeneous at the moment of admission in the post-anesthesia care unit (p-value=0.008). The experimental group presented higher prevalence of subjects with dyspnea and breathing difficulties. In relation to the peripheral oxygen saturation, it showed that the groups were heterogeneous over time (p-value=0.000). Analyzing the vital signs, it had statistical significance regarding to the systolic blood pressure at the admission (p-value=0.033), and the control group presented higher frequency of subjects with hypertension, whereas most of the subjects from the experimental group presented hypotension. At the first hour of permanence in the post-anesthesia care unit, both groups were heterogeneous in relation to the heart rate and body temperature, with p-value higher than 0.05. By the time 30 and 60 minutes, all the subjects had normal respiratory rate. Analyzing the variables, it was possible to verify that there was no significant difference between the groups, in relation to the alterations of the parameters of consciousness, circulation, body temperature, systolic blood pressure, heart rate and respiratory rate, at the first hour of permanence in the post-anesthesia care unit. There was significant influence of the length of time of the surgery on consciousness (p-value=0.027), and the age on the heart rate. It showed that every 10 years, the heart rate decreases 3% (p-value=0.033). The patients who presented drop in oxygen saturation, had 0.35 times more likely to develop changes in circulatory parameters than those who did not have decrease in the oxygen saturation. Also, these patients had decrease of 7% in the respiratory rate when compared to the subjects who did not presented drop in oxygen saturation. Conclusion: It is essential that nurses recognize and monitors the characteristics that define possible complications that can occur in the post-anesthesia care unit, in order to prevent and reduce risks to the patient.